2016
DOI: 10.1523/jneurosci.3685-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Fixation Reveals Latent Sensorimotor Processes in the Superior Colliculus

Abstract: Executive control of voluntary movements is a hallmark of the mammalian brain. In the gaze-control network, this function is thought to be mediated by a critical balance between neurons responsible for generating movements and those responsible for fixating or suppressing movements, but the nature of this balance between the relevant elements-saccade-generating and fixation-related neuronsremains unclear. Specifically, it has been debated whether the two functions are necessarily coupled (i.e., push-and-pull) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

7
2

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…The ability of a laminar probe to record simultaneously the activities of neurons along this axis revealed that there is a gradual transition from visual to visuomotor to motor neurons with depth but the vast majority are visuomotor (Figure 4). We also demonstrated previously 30 and discussed above that putative motor neurons can exhibit a visual response under certain conditions. Thus, we prefer to avoid making a distinction between visuomotor and motor neurons.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The ability of a laminar probe to record simultaneously the activities of neurons along this axis revealed that there is a gradual transition from visual to visuomotor to motor neurons with depth but the vast majority are visuomotor (Figure 4). We also demonstrated previously 30 and discussed above that putative motor neurons can exhibit a visual response under certain conditions. Thus, we prefer to avoid making a distinction between visuomotor and motor neurons.…”
Section: Discussionsupporting
confidence: 84%
“…While we don’t dispute this hypothesis, we also can’t refute the possibility that this pathway’s central role may be to relay the visual signal to visuomotor neurons. It may even be relayed to putative motor neurons in the SC but other inhibitory inputs may suppress its expression, and the removal of inhibition could unmask the sensory burst 30 . It is also possible that extracollicular sources may contribute to or augment the visual response relayed from the superficial layers.…”
Section: Discussionmentioning
confidence: 99%
“…6). A related alternative explanation is that a movement is initiated specifically when movement-only neurons are active, but most neurons in sensorimotor structures like SC and FEF span a continuum between visuomovement activity and movement activity 1,34,35 . In fact, antidromically identified tectoreticular neurons that presumably drive saccade generation exhibit both visual and premotor bursts 7 .…”
Section: Perspectives On the Role Of Temporal Structurementioning
confidence: 99%
“…We would like to emphasize that the observed results -preparatory motor potential, reduced threshold, 508 accelerated activity dynamics -are most likely indirect effects of the trigeminal blink reflex, via inhibition 509 of the OPNs, and not directly due to the reflex itself. Prior work has shown that the activity of SC neurons 510 is not affected by the BREM produced during fixation (Goossens and Van Opstal, 2000a; Jagadisan and 511 Gandhi, 2016). For blinks produced after the saccade target is presented, some SC neurons in fact exhibit 512 attenuation (Goossens and Van Opstal, 2000a), although we did not see it in our dataset (and even if that 513 did happen, it is counter-intuitive to and does not explain the motor potential and acceleration of activity).…”
Section: The Role Of Sc and Brainstem In Saccade Execution 479mentioning
confidence: 99%